Cardiovascular prevention 2022. Russian national guidelines - S. A. Boytsov; N. V. Pogosova; A. A. Ansheles; V. A. Badtieva; T. V. Balakhonova; O. L. Barbarash; Yu. A. Vasyuk; N. G. Gambaryan; G. E. Gendlin; S. P. Golitsyn; O. M. Drapkina; L. Yu. Drozdova; et al. (Российский кардиологический журнал, 2023)
Russian Society of Cardiology, National Society of Preventive Cardiology